2011
DOI: 10.1021/ci100368t
|View full text |Cite
|
Sign up to set email alerts
|

Docking-Based Comparative Intermolecular Contacts Analysis as New 3-D QSAR Concept for Validating Docking Studies and in Silico Screening: NMT and GP Inhibitors as Case Studies

Abstract: The significant role played by docking algorithms in drug discovery combined with their serious pitfalls prompted us to envisage a novel concept for validating docking solutions, namely, docking-based comparative intermolecular contacts analysis (dbCICA). This novel approach is based on the number and quality of contacts between docked ligands and amino acid residues within the binding pocket. It assesses a particular docking configuration on the basis of its ability to align a set of ligands within a correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 116 publications
0
79
0
Order By: Relevance
“…As a result, it is common to include explicit water molecules in computational drug design [6][8]. The careful consideration of hydration sites has been shown to aid the predictability of 3D QSAR models, [9][11] ensure stable simulations with molecular dynamics [12], and improve the accuracy of rigorous free energy calculations [13]. Continuum solvent models have also been reported to improve with the addition of explicit water molecules [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is common to include explicit water molecules in computational drug design [6][8]. The careful consideration of hydration sites has been shown to aid the predictability of 3D QSAR models, [9][11] ensure stable simulations with molecular dynamics [12], and improve the accuracy of rigorous free energy calculations [13]. Continuum solvent models have also been reported to improve with the addition of explicit water molecules [14].…”
Section: Introductionmentioning
confidence: 99%
“…A popular strategy in rational drug design is to modify a ligand so that it displaces an ordered water molecule into the bulk solvent [5], [11], [22], [23]. This is due to the favorable entropic gain that can result by increasing the water molecule's translational and orientational degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of HIV protease (PDB ID: 1T3R) was collected from RCSB-Protein Data Bank. Self-docking is one of the approaches to validate the molecular docking method [59] in which bound ligand is docked at the catalytic site of protein molecule and the conformer of the original bound ligand is superimposed to the docked poses to calculate root mean square deviation (RMSD) values. It is reported that low RMSD (<2 Å) value of original bound ligand validates the docking procedure [59].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…These modeling efforts aim at establishing pharmacophore models to be used as 3D search queries for virtual screening of potential MERS‐CoV 3CL pro inhibitors. The methods used here were developed previously by our group: the QSAR‐guided pharmacophore modeling and the docking‐based comparative intermolecular contacts analysis (dbCICA) pharmacophore modeling . Both modeling approaches have been used successfully to identify potent inhibitors against several drug targets .…”
Section: Introductionmentioning
confidence: 99%
“…The methods used here were developed previously by our group: the QSAR‐guided pharmacophore modeling and the docking‐based comparative intermolecular contacts analysis (dbCICA) pharmacophore modeling . Both modeling approaches have been used successfully to identify potent inhibitors against several drug targets . The identified hits were tested in vitro for their inhibitory activity against the 3CL pro enzymes from HKU4‐CoV and MERS‐CoV.…”
Section: Introductionmentioning
confidence: 99%